“Facial nerve monitoring and Diffusion Tensor Imaging in vestibular schwannoma surgery in low- and middle-income countries -A systematic review of financial consideration”. - Singh, Dr Akshay Patidar , Dr Nisha Bhatta, Dr. Harsh Joshi, Dr Mayank (South Eastern European Journal of Public Health, 2025)
There are differences in surgical care comparing the nations with high, low, and moderate incomes. Vestibular Schwannoma surgery techniques have undergone lot of revolution in the last century. IONM are being widely used in developed countries and being propagated in LMICs with great enthusiasm. The goal of the current investigation was to systematically review the published literature and to find out the costs and utility of vestibular schwannoma surgery performed with the aid of IONM and DTI in resources poor countries. Methods: -Direct basic costs for surgery and cost of IONM and DTI were calculated from previous studies. Cost of IONM and DTI is added to overall cost if they are used. To assess the impact of these modern technologies ,3 macro-scenarios were considered: (1) Vestibular schwannoma surgery without IONM (2) Vestibular schwannoma surgery with IONM (3) Vestibular schwannoma surgery with IONM and DTI. To calculate the average cost, probability model was used and it was assumed that 100 cases were operated in each scenario and average cost were calculated after including complications and their management. Results: The average cost in the group without IONM was highest (91,699 USD) and in the IONM and DTI group was lowest (83,983 USD) and was 84,686 USD in IONM group. The additional cost of IONM and IONM with DTI cost was 0.414% and 0.558% of total cost respectively per case. Discussion: - In the setting of vestibular schwannoma surgery, IONM with or without DTI is more cost-effective considering impact of facial nerve injury than surgery without IONM. Conclusion: - This analysis shows that the cost-effectiveness of the vestibular schwannoma surgery with IONM and DTI for facial nerve injury and should be encouraged.